Transition from hospital to home: Parents’ perception of their preparation and readiness for discharge with their preterm infant - Aydon, L.; Hauck, Yvonne; Murdoch, J.; Siu, D.; Sharp, M. (Wiley-Blackwell Publishing, 2017)
Aims and objectives: To explore the experiences of parents with babies born between 28–32 weeks’ gestation during transition through the neonatal intensive care unit and discharge to home. Background: Following birth of a preterm baby, parents undergo a momentous journey through the neonatal intensive care unit prior to their arrival home. The complexity of the journey varies on the degree of prematurity and problems faced by each baby. The neonatal intensive care unit environment has many stressors and facilitating education to assist parents to feel ready for discharge can be challenging for all health professionals. Design: Qualitative descriptive design. Methods: The project included two phases, pre‐ and postdischarge, to capture the experiences of 20 couples (40 parents), whilst their baby was a neonatal intensive care unit inpatient and then after discharge. Face‐to‐face interviews, an online survey and telephone interviews were employed to gather parent's experiences. Constant comparative analysis was used to identify commonalities between experiences. Recruitment and data collection occurred from October 2014–February 2015. Results/Findings: Overlapping themes from both phases revealed three overarching concepts: effective parent staff communication; feeling informed and involved; and being prepared to go home. Conclusion: Our findings can be used to develop strategies to improve the neonatal intensive care unit stay and discharge experience for parents. Proposed strategies would be to improve information transfer, promote parental contact with the multidisciplinary team, encourage input from fathers to identify their needs and facilitate parental involvement according to individual needs within families. Relevance to clinical practice: Providing information to parents during their time in hospital, in a consistent and timely manner is an essential component of their preparation when transitioning to home.